2012
DOI: 10.1007/s10661-012-2637-6
|View full text |Cite
|
Sign up to set email alerts
|

Lead (Pb) quantification in potable water samples: implications for regulatory compliance and assessment of human exposure

Abstract: Assessing the health risk from lead (Pb) in potable water requires accurate quantification of the Pb concentration. Under worst-case scenarios of highly contaminated water samples, representative of public health concerns, up to 71-98 % of the total Pb was not quantified if water samples were not mixed thoroughly after standard preservation (i.e., addition of 0.15 % (v/v) HNO(3)). Thorough mixing after standard preservation improved recovery in all samples, but 35-81 % of the total Pb was still un-quantified i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 16 publications
1
30
1
Order By: Relevance
“…The estimated risk associated to tap water exposure with multiple imputation was similar to the one estimated with missing data or with replacement of values by raw data (data not shown). If, as observed by Triantafyllidou et al (2013) at higher lead water concentrations, water lead measurements were underestimated in our study due to samples transfer, the strength of the association between lead in water and blood would be overestimated. The effect of tap water has been studied previously (Brown and Margolis, 2012;Lanphear et al, 1998a;Levallois et al, 2013;Miranda et al, 2007;Renner, 2010).…”
Section: Tap Watermentioning
confidence: 56%
“…The estimated risk associated to tap water exposure with multiple imputation was similar to the one estimated with missing data or with replacement of values by raw data (data not shown). If, as observed by Triantafyllidou et al (2013) at higher lead water concentrations, water lead measurements were underestimated in our study due to samples transfer, the strength of the association between lead in water and blood would be overestimated. The effect of tap water has been studied previously (Brown and Margolis, 2012;Lanphear et al, 1998a;Levallois et al, 2013;Miranda et al, 2007;Renner, 2010).…”
Section: Tap Watermentioning
confidence: 56%
“…It is probable, as in other areas, that Broken Hill/Mt Isa Pb was used in the manufacture of the plumbing materials [ 12 , 13 ]. In addition the high temperatures of this area may have enhanced the solubility of Pb from the brass fittings [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…If the tank is of polypropylene or other plastic, these may also contain traces of Pb but the tap could also contribute Pb if it is brass. As temperature and pH play an important role in the metal content of water, these could be additional contributing factors [ 14 ]. Rainwater commonly has a lower pH than neutral.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 It has been demonstrated that particulate Pb (e.g., flakes from solder, brass, or Pb pipes) can be significant under some circumstances. 32 However, because flow rates from the pumps are low, and because pitcher-pump systems contain few fittings ( Figure 1) and no piped distribution system, it may be reasonable to assume that most Pb is in the dissolved (not particulate) form. Thus, the measurements obtained via the field procedure must be considered lower bounds of the total Pb concentrations, but are likely to be reasonable estimates of those total concentrations.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%